Improvement of methodological approaches to accounting of household wastewater supplied to treatment facilities in settlements of the Republic of Belarus - Holad, Yuliya V.; Dubianok, Sniazhana A. (Journal of the Belarusian State University. Ecology, 2022)
The centralized sewage systems (sewerage) of settlements receive domestic wastewater from consumers (population) and subscribers (legal entities, individual entrepreneurs), as well as their own domestic wastewater from enterprises of water supply and sewerage services and housing and communal services. At the same time, centralized sewerage systems (sewerage systems) are designed not only for the transportation of household, but also for industrial wastewater, which can also have a significant impact on the quantitative and qualitative composition of wastewater entering the treatment facilities of the settlement.Improvement of methodological approaches to the accounting of domestic wastewater includes an increase in the level of accounting for both quantitative and qualitative characteristics of domestic wastewater.Currently, there is no reliable accounting of household wastewater entering the treatment facilities of settlements: their volume from the population is determined by the non-routine (calculation) method - 100 % of the volume of water consumption, from subscribers - as a rule, it is also carried out by the non-instrumental method, which is often incomparable with the volumes of water used by subscribers and consumers for household and drinking needs. The quality control of domestic wastewater is not carried out due to the lack of requirements for standardization of domestic wastewater. It should be noted that the balance holders of centralized wastewater disposal (sewerage) systems cannot affect the quantitative and qualitative composition of domestic wastewater, and therefore it becomes necessary to develop a methodology for calculating the permissible concentrations of pollutants in wastewater, which, in addition to industrial wastewater , will take into account the quantitative and qualitative characteristics of household wastewater discharged to centralized wastewater disposal (sewerage) systems by subscribers and consumers, and then to wastewater treatment plants in settlements of the Republic of Belarus.
Keywords: domestic wastewater; treatment facilities; metering device; polluting substances